Synthesis and chractrisation of di azo dyes using 7-hydroxy-4-methyl coumarin as a coupling compound (Journal of Hama University, 2024)
AbstractA heterocyclic diazo dye containing coumarin structure, which is:7-hydroxy-4-methyl-8-(4-nitrophenylazo)-6-(4-nitrophenylazo) coumarin, has been synthesized by diazotization a double molar amount of the aromatic amine: 4-nitroaniline. Then coupling reaction of diazonium resulting salt with one molar amount of 7-hydroxy -4- methyl coumarin was done ,the purity of this dye was verified by measuring the melting point and TLC, Purified dye was characterized by spectroscopic methods such as : 1HNMR, IR
Keywords: Coumarin, Azo dyes, diazotization